Derivative of sawtooth - interpretation of result

15 次查看(过去 30 天)
Hi everyone. I derived a sawtooth function:
with the following code:
syms t
x=t*(heaviside(t)-heaviside(t-3));
y=diff(x);
The result is: y = heaviside(t) - heaviside(t - 3) - t*(dirac(t - 3) - dirac(t)). I don't understand why the delta Dirac is multiplied per t. I know that x(t)*delta(t-3)=x(0)*delta(t-3), but x(0)=0 thus, for matlab x(0)*delta(t-3)=0.
Thank you very much.

回答(1 个)

David Goodmanson
David Goodmanson 2017-7-3
编辑:David Goodmanson 2017-7-3
Hello Gennaro,
This is just the formula for the derivative of a product,
t * ( heaviside(t) -heaviside(t-3) )
where
d/dt heaviside(t) = delta(t) and d/dt heaviside(t-3) = delta(t-3).
And as a distribution,
Integral x(t)*delta(t-3) dt = x(3)
and (assuming limits of integration include t=3)
Integral x(3)*delta(t-3) dt = x(3) * Integral delta(t-3) dt = x(3)
so effectively
(x(t)-x(3))*delta(t-3) = 0
not
(x(t)-x(0))*delta(t-3) = 0
  2 个评论
Gennaro Arguzzi
Gennaro Arguzzi 2017-7-3
编辑:Gennaro Arguzzi 2017-7-3
Hi @David Goodmanson, I don't understand the graphic meaning of t*delta(t-3). When my professor evaluate the derivative, he wrote only the term d(t)/dt*delta(t-3)=1*delta(t-3). The graphic meaning of delta(t-3) is clear, but t*delta(t-3) is unclear for me. PS: I don't know the distributions. Thank you very much.
David Goodmanson
David Goodmanson 2017-7-3
编辑:David Goodmanson 2017-7-4
Hello Gennaro, I will try to give a better version of what is in the answer. The delta "function" delta(t) is a kind of spike that has a nonzero value only at t=0, and the total area under its curve = 1. The translated function delta(t-3) is nonzero only when its argument is zero, so at t=3.
For the product t*delta(t-3), t=3 is the only value that matters and gives something nonzero, so you can substitute and effectively
t*delta(t-3) = 3*delta(t-3)
You can also look at what happens when you integrate across the location of the delta function.
fundamental definition:
Integral g(t)*delta(t-t0) dt = g(t0) for any g(t)
so if g(t) = t,
Integral t*delta(t-3) dt = 3
but
Integral 3*delta(t-3) dt = 3 (delta function has area 1)
so effectively
t*delta(t-3) = 3*delta(t-3)
If your prof wrote that effectively
t*delta(t-3) = delta(t-3)
I would say he or she made a mistake.

请先登录,再进行评论。

类别

Help CenterFile Exchange 中查找有关 Creating and Concatenating Matrices 的更多信息

标签

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!

Translated by